Balance control impairments in Fabry disease - Peultier-Celli, Laetitia; Jaussaud, Roland; Kaminsky, Pierre; Deibener-Kaminsky, Joëlle; Feillet, François; Perrin, Philippe (Frontiers in Neurology, 2022)
Background: Fabry disease (FD) is a rare inherited lysosomal storage disorder caused by the deficiency of the enzyme alpha-galactosidase A. This deficiency leads to an accumulation of glycosphingolipids leading to progressive and multisystemic disease, including renal, cardiac and neurological damages. FD may also have neuro-otological and visual impairments, which can generate postural control alterations, inner ear and vision being involved in this function. This study aimed to evaluate the impact of FD on postural control. Methods: Fourteen adult patients (8 males/6 females, mean age = 37.6 + 11.4 years) and two children (mean age = 11 years) with FD and 19 healthy adults (12 males/7 females, mean age = 36.5 + 16.9 years) and two healthy children (mean age = 10.5 years) took part in this study. Postural control was evaluated by a sensory organization test combining three visual situations (eyes open, eyes closed, sway referenced visual surround motion) with two platform situations (stable platform, sway referenced platform motion), aiming to calculate a composite equilibrium score (CES), a high score being representative of good postural control. Somatosensory (RSOM), visual (RVIS) and vestibular (RVEST) contributions to postural control were calculated, a low score reflecting a poor use of the indicated sensory input. Results: The CES was lower in adult patients with FD compared to healthy subjects (p<0.001). RVIS (p=0.001) and RVEST (p=0.003) were lower in FD patients compared to the control group, whereas no difference in RSOM was observed. Conclusion: Inner ear and visual pathologies associated with central nervous system impairments are factors of postural control impairments. Physical activities, which can also be rehabilitative, by maintaining or increasing the weight of proprioception, may help diminish dependency to altered sensorial inputs.